Radar-climatology of Delhi and neighbourhood : spatial and. . diurnal variations of precipitation echo distribution (MAUSAM, 1964)
The paper presents a radar-climatological analysis of the New Delhi radar data for a period of 31 months (December 1957 to June 1960). The object is to investigate the space and time variations of precipitation echo distribution within a range of 200 miles round the radar station. The distribution of areal coverage as well as that of the heights of precipitation echoes in the area have been studied both on a month-by-month and a seasonal basis. The diurnal variations of areal and height distributions have also been studied for all the months.